PELATIHAN PENULISAN BLOG BAGI PARA GURU SMA NEGERI 1 WIDODAREN NGAWI - ardhi wijayanto; Bambang Harjito (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has caused restrictions on community activities, including teaching and learning activities in schools that must be held online. This is also experienced by SMA Negeri 1 Widodaren Ngawi which carries out Distance Learning (PJJ) activities. PJJ activities in schools have a number of challenges ranging from limited facilities and infrastructure, the lack of maximum interaction between teachers and students, and the difficulty of teachers to monitor the condition of their students. For this reason, the creativity of teachers in implementing PJJ is required, one form of this creativity is how to convey material to the students. Submission of material in distance learning is done using information technology. Blogs can be an alternative medium for delivering learning materials. As an online medium, blogs have the advantage that they can be accessed anytime, from anywhere, and by anyone through an internet connection. Therefore, blogs are considered suitable as a medium to support distance learning activities. At SMA Negeri 1 Widodaren, only a few teachers use blogs as a medium to deliver learning materials. In this community service activity, teachers will be given training to create and manage blogs as a medium for delivering learning materials to students. After being given the training, all the teachers can create a blog to share the subject matter.